Bodhisattvabhūmiḥ - Asaṅga; Dutt, Nalinaksha (Bhoṭadeśīya-Saṃskr̥ta-granthamālā, 1978)
Treatise on the Yogācāra philosophy; chapter 15 deals with the metaphysical considerations about the state of enlightenment; critical edition.